PENURUNAN KADAR FENOL PADA LIMBAH CAIR NON-DESTRUCTIVE TESTING (NDT) MENGGUNAKAN METODE ADSORPSI (Jurnal Kesehatan Siliwangi, 2021)
The production liquid waste contains phenol content from the unit Non-Destructive Testing (NDT) because it uses solvents. Based on the results of laboratory tests conducted on the liquid waste NDT PT. Y found that the phenol content was 2.33 mg/L with a quality standard of 0.5 mg/L based on the Minister of Environment Regulation Number 5 of 2014 concerning Wastewater Quality Standards. The purpose of this study was to determine the effect of variations in the thickness of the adsorbent media of zeolite and activated carbon in reducing phenol levels in wastewater. This research is experimental with are search design pretest-posttest without control. The sample in this study was liquid waste NDT PT. Y. The sampling technique is grab sampling. The test was repeated 6 times using aflow system batch. Statistical testing using one way ANOVA showed a significant difference between variations in the thickness of the zeolite adsorbent media and activated carbon in reducing phenol levels because it had a p value < α (0.035 < 0.05). The average phenol content after passing through the adsorbent medium at a thickness of 40 cm is 0.99 mg/L with a percentage decrease of 63%, at a thickness of 60 cm is 0.60 mg/L with a percentage decrease of 77% and at a thickness of 80 cm, namely 0.28 mg/L with a percentage decrease of 89%. The thickness that is most is 80 cm thick.